God - "Ward, Keith" (Oxford, 2007)
Inspired and impassioned, this new book charts the path of humanity's great spiritual odyssey: the search for God. Along this ancient and winding road, the reader will encounter philosophers from Plato to Wittgenstein and religions from Judaism to the Hindu tradition, interspersed with divine influences from Classical Greece, Romantic poetry, and the occasional scene from 'Alien'. Leading the way through this minefield is acclaimed philosopher-theologian Kith Ward, blending the sublime and the eclectic in a narrative which offers wit, erudition and moments of genuine pathos. As a survey of the different manifestations of God through the centuries, and an examination of humanity's search for the divine, this is an engaging and informative book. As a deeply moving testament to our endless capacity for spiritual hope, it is compulsive reading for anyone interested in, or embarking on, the great quest for meaning.
Keywords: God